2009
DOI: 10.1104/pp.109.139758
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diglycosyl Lipids in Photosynthesis and Membrane Lipid Homeostasis in Arabidopsis

Abstract: The galactolipid digalactosyldiacylglycerol (DGD) is an abundant thylakoid lipid in chloroplasts. The introduction of the bacterial lipid glucosylgalactosyldiacylglycerol (GGD) from Chloroflexus aurantiacus into the DGD-deficient Arabidopsis (Arabidopsis thaliana) dgd1 mutant was previously shown to result in complementation of growth, but photosynthetic efficiency was only partially restored. Here, we demonstrate that GGD accumulation in the double mutant dgd1dgd2, which is totally devoid of DGD, also complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 47 publications
1
48
1
Order By: Relevance
“…It has been shown that replacing DGDG with GGDG in the dgd1 mutant can restore plant growth and chloroplast shape but not photosynthesis (Hölzl et al, 2006(Hölzl et al, , 2009. Together with our data, this shows that the dgd1 phenotypes are caused by three factors.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It has been shown that replacing DGDG with GGDG in the dgd1 mutant can restore plant growth and chloroplast shape but not photosynthesis (Hölzl et al, 2006(Hölzl et al, , 2009. Together with our data, this shows that the dgd1 phenotypes are caused by three factors.…”
Section: Discussionsupporting
confidence: 83%
“…When observed by electron microscopy, instead of being spindle-shaped, like wild-type chloroplasts, dgd1-1 chloroplast envelopes are usually more rounded, but the thylakoids remain elongated, resulting in bent thylakoids and large thylakoid-free stromal areas (Dörmann et al, 1995;Hölzl et al, 2009). As shown in Figure 7, the dgd1-2 allele showed the same phenotype as the dgd1-1 allele, whereas chloroplasts in the aos and coi1-30 mutants had the same morphology as the wild-type chloroplasts, and all double mutants exhibited rounded chloroplasts with bent thylakoids, as in the dgd1 mutants.…”
Section: Reduced Photosynthesis and Altered Chloroplast Morphology Armentioning
confidence: 99%
See 1 more Smart Citation
“…In Synechococcus, accumulation of ββGlcGDG by introducing β-GlcT could not complement the knockout of dgdA (Maida and Awai, 2016). Considering that ββGlcGDG can partially complement photosynthetic efficiency with increased susceptibility of photosystem II to photodamage (Hölzl et al, 2009) and that dgdA mutants of Synechocystis have a similar phenotype (Mizusawa et al, 2009a(Mizusawa et al, , 2009b, this result implies that αβDGDG has specific roles in the recovery from photodamage.…”
Section: Molecular Species and Configuration Of The Sugar Head In Digmentioning
confidence: 95%
“…This led to various defects in the mutant, especially the dwarf phenotype, mainly because of overproduction of oxylipin and lignification of the phloem cap (Lin et al, 2016). These phenomena were partially complemented by introducing Chloroflexus aurantiacus glycosyltransferase (β-GlcT) (Hölzl et al, 2006(Hölzl et al, , 2009, which synthesizes…”
Section: Molecular Species and Configuration Of The Sugar Head In Digmentioning
confidence: 99%